Activation of TREM2 attenuates neuroinflammation via PI3K/Akt signaling pathway to improve postoperative cognitive dysfunction in mice. (15th November 2022) - Han, Xue; Cheng, Xiaolei; Xu, Jiyan; Liu, Yujia; Zhou, Jiawen; Jiang, Linhao; Gu, Xiaoping; Xia, Tianjiao
Abstract: Postoperative cognitive dysfunction (POCD) is a common postoperative complication involving the central nervous system, but the underlying mechanism is not well understood. Neuroinflammation secondary to surgery and anesthesia is strongly correlated with POCD. A key aspect of neuroinflammation is microglia activation. Triggering receptor expressed on myeloid cells (TREM)2, which is highly expressed in microglia, is an innate immune receptor that modulates microglia function. In this study we investigated the role of TREM2 in cognitive impairment and microglia-mediated neuroinflammation using a mouse model of POCD and in vitro systems. We found that hippocampus-dependent learning and memory were impaired in POCD mice, which was accompanied by activation of microglia and downregulation of TREM2. Pretreatment with the TREM2 agonist heat shock protein (HSP)60 inhibited surgery-induced microglia activation and alleviated postoperative cognitive impairment. In BV2 microglial cells, the phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002 significantly reversed the attenuation of TREM2 activation on lipopolysaccharide (LPS)-induced neuroinflammation and abrogated the protective effect of activated TREM2 against LPS-induced neuronal injury in a microglia/neuron coculture system. Accordingly, the beneficial effects of TREM2 activation on cognitive function were reversed by preoperative administration of LY294002 in the POCD mouse model. These results demonstrate that TREM2 is involved in the regulation of the inflammatory response mediated by microglia and cognitive impairment following surgery. Activation of TREM2 can attenuate neuroinflammation by modulating PI3K/protein kinase B (Akt) signaling, thereby alleviating postoperative learning and memory deficits. Highlights: Expression of TREM2 were downregulated in POCD model. TREM2 activation inhibits microglia-mediated neuroinflammation and improves postoperative cognitive impairment. PI3K inhibitor abrogated the protective effect of activated TREM2 against LPS-induced neuronal injury. PI3K/Akt signaling mediated the protective function of TREM2 in POCD model.